SOME MEDICINAL PLANTS BELONGING TO THE AMARANTH FAMILY - Abdukhalilova Madinakhon (Journals Park Publishing, 2023)
This article talks about medicinal plants belonging to the amaranth family and the importance of these plants in maintaining human health.
Keywords: Salsolin, spasm, hypertension, oblepikha, cancer.